Social Media Recruitment as a Potential Trigger for Vulnerability: Multistakeholder Interview Study - Nina Matthes; Theresa Willem; Alena Buyx; Bettina M Zimmermann (JMIR Human Factors)
Abstract BackgroundMore clinical studies use social media to increase recruitment accrual. However, empirical analyses focusing on the ethical aspects pertinent when targeting patients with vulnerable characteristics are lacking. ObjectiveThis study aims to explore expert and patient perspectives on vulnerability in the context of social media recruitment and seeks to explore how social media can reduce or amplify vulnerabilities. MethodsAs part of an international consortium that tests a therapeutic vaccine against hepatitis B (TherVacB), we conducted 30 qualitative interviews with multidisciplinary experts in social media recruitment (from the fields of clinical research, public relations, psychology, ethics, philosophy, law, and social sciences) about the ethical, legal, and social challenges of social media recruitment. We triangulated the expert assessments with the perceptions of 6 patients with hepatitis B regarding social media usage and attitudes relative to their diagnosis. ResultsExperts perceived social media recruitment as beneficial for reaching hard-to-reach populations and preserving patient privacy. Features that may aggravate existing vulnerabilities are the acontextual point of contact, potential breaches of user privacy, biased algorithms disproportionately affecting disadvantaged groups, and technological barriers such as insufficient digital literacy skills and restricted access to relevant technology. We also report several practical recommendations from experts to navigate these triggering effects of social media recruitment, including transparent communication, addressing algorithm bias, privacy education, and multichannel recruitment. ConclusionsUsing social media for clinical study recruitment can mitigate and aggravate potential study participants’ vulnerabilities. Researchers should anticipate and address the outlined triggering effects within this study’s design and proactively define strategies to overcome them. We suggest practical recommendations to achieve this.